2017
DOI: 10.3390/coatings7050068
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of Plasma Sprayed Thermal Barrier Coatings

Abstract: Thermal spray coatings (TSCs) have complex microstructures and they often operate in demanding environments. Plasma sprayed (PS) thermal barrier coating (TBC) is one such ceramic layer that is applied onto metallic components where a low macroscopic stiffness favors stability by limiting the stresses from differential thermal contraction. In this paper, the Young's modulus of TBC top coat, measured using different techniques, such as four-point bending, indentation and impulse excitation is reported, along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
(92 reference statements)
1
11
1
Order By: Relevance
“…The elastic modulus along the in-plane and out-of-plane direction is 144± 12and 109± 7GPa, respectively. Both values are significantly higher than the global modulus (10-70 GPa) of the APS TBCs reported in the literature [11,[20][21][22][23][24] . The difference is expected as the characteristic volume of the material that undergoes deformation during micro-cantilever bending is only in the range of ~ 60 -110 μm 3 , which is expected to contain far less defects than the macroscale TBC samples used for determination of the global modulus.…”
Section: Elastic Moduluscontrasting
confidence: 60%
“…The elastic modulus along the in-plane and out-of-plane direction is 144± 12and 109± 7GPa, respectively. Both values are significantly higher than the global modulus (10-70 GPa) of the APS TBCs reported in the literature [11,[20][21][22][23][24] . The difference is expected as the characteristic volume of the material that undergoes deformation during micro-cantilever bending is only in the range of ~ 60 -110 μm 3 , which is expected to contain far less defects than the macroscale TBC samples used for determination of the global modulus.…”
Section: Elastic Moduluscontrasting
confidence: 60%
“…In the literature it is also proposed to shaped more porous TBC in order to reduce the thermal conductivity and reach low value as 0.4 W/mK for porosity higher than 30%vol [5]. Another important step for such ceramics is to evaluate their mechanical properties in order to bring their multifunctional properties on metallic substrates exposed to severe environment [6]. Many processes such as template method, slip casting, gel casting, direct foaming or partial sintering of powder [7][8][9][10] have already been used to produce porous ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…It has thus been of interest to examine the change in microstructure, stiffness, and thermal properties of the APS YSZ system subjected to continuous and cyclic thermal exposures. A large portfolio of scientific literature exists for both such attributes with exposure of free‐standing sprayed bodies to various temperatures and times . Specifically, a number of studies have reported the variation in the elastic modulus with sintering and attempted correlation with the variation in elastic modulus and microstructure evolution with sintering, but most of these studies have been carried out beyond 1000°C.…”
Section: Introductionmentioning
confidence: 99%
“…A large portfolio of scientific literature exists for both such attributes with exposure of free-standing sprayed bodies to various temperatures and times. [16][17][18][19][20][21] Specifically, a number of studies have reported the variation in the elastic modulus with sintering and attempted correlation with the variation in elastic modulus and microstructure evolution with sintering, but most of these studies have been carried out beyond 1000°C. Thomson et al 22,23 have shown the variation in bending modulus by cantilever bending of APS 8YSZ coating after sintering at temperatures ranging from 1000°C to 1400°C.…”
Section: Introductionmentioning
confidence: 99%